Characterization and Evaluation of Heat–Moisture-Modified Black and Red Rice Starch: Physicochemical, Microstructural, and Functional Properties - Victor Herbert de Alcântara Ribeiro; Mario Eduardo Rangel Moreira Cavalcanti-Mata; Raphael Lucas Jacinto Almeida; Virgínia Mirtes de Alcântara Silva (Foods, 2023)
This study sought to evaluate starch from black and red rice modified by heat–moisture, investigating the extraction yield, starch and amylose content, color, and phenolic compounds. The water and oil absorption capacity, whole milk and zero lactose absorption index, syneresis index, and texture were also analyzed. Microstructural analysis included Fourier transform infrared spectroscopy, X-ray diffraction, and scanning electron microscopy. The heat–moisture treatment (HMT) reduced the extraction yield and the starch and amylose content, with native black rice starch having the highest values for these parameters. The modification also affected the color and phenolic compounds of the starch, making it darker and changing its appearance. The modification improved the absorption of water, oil, and milk, reducing syneresis and increasing stability during storage. The starch surface was altered, especially for modified black rice starch, with larger agglomerates. The type of starch also changed from A to Vh, with lower relative crystallinity. The textural properties of modified red rice starch were also significantly altered. The HMT proved to be a viable and economical option to modify the analyzed parameters, influencing the texture and physicochemical properties of pigmented rice starch, expanding its applications, and improving its stability during storage at temperatures above 100 °C.